The history of New Zealand English - A R Beckeyeva (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2013)
The article is dedicated to the peculiarities of the New Zealand English making, in particular, the main historical background is researched. The early national and cultural peculiarities of the New Zealand English are considered.